Annealing effects on the electrical properties of spin coated poly (3-hexylthiophene) (P3HT) thin films. (April 2017) - Aruna, P.; Joseph, C.M.
Abstract: Poly (3-hexylthiophene-2, 5-diyl) (P3HT) thin films were prepared using spin coating technique and the effect of annealing on the bias switching for memory applications were studied. Due to annealing, the threshold voltage for switching was reduced considerably. In bias switching, threshold voltage was least for the sample annealed at 100 °C. Addition of phenyl-C61 -butyric acid-methyl-ester (PCBM) into P3HT also reduced the threshold voltage. It was also found that the devices with gold (Au) top electrode switched at a lower threshold voltage compared to their aluminium (Al) counterparts.